Mortality Associated Factors in VLBW Preterm Newborns between 2002-2011 in a Peruvian Hospital - Gutiérrez, M. E.; Matzumura, G.; Olivos, D.; Loza, C.; Rivera, F.; Webb, V. (International Journal of Pediatrics and Child Health, 2016)
Objective: Describe the trend in mortality and identify risk factors for diminished survival in preterm very low birth infants (VLBW) born at the Hospital Nacional Cayetano Heredia (HNCH) between 2002 and 2011. Methods: Retrospective cohort that includes 549 VLBW babies born at the HNCH registered on a database created for a multicentric network between 2002 and 2011. The chi-square test was used to determine associated factors with mortality (p<0.05). Survival analysis was performed using the Kaplan-Meier curves with primary outcome being death during hospital stay. Log rank test and Wilcoxon test were then applied to these curves. A multivariate analysis using the Cox Model was performed. Results: Overall mortality rate was 40.80%, 60.71% of which was attributed to early mortality and 39.29% to late mortality. Associated factors were gestational age (HR: 0.85; IC 95%: 0.18-0.90; p<0.0001), prenatal steroids (HR: 1.46; IC 95% 1.09-1.95; p< 0.011), neonatal resuscitation (HR: 1.50; IC 95% 1.06-2.13; p<0.021), early sepsis (HR: 1.52; IC 95%: 1.01-2.28; p<0.043), respiratory distress syndrome (RDS) (HR: 8.47; IC 95%: 3.50-20.46; p<0.0001) and CPAP (continuous positive airway pressure) (HR: 0.25; IC 95%: 0.18-0.34; p<0.0001). Factors associated with neonatal survival were gestational age, neonatal resuscitation, early sepsis, RDS and CPAP. Conclusion: Mortality in VLBW infants has declined considerably in this Peruvian hospital in the 2002-2011 period. The risk factor with the highest association to mortality in this population was RDS.